PENGARUH KARAKTERISTIK KETUA KOMITE AUDIT TERHADAP PILIHAN AUDITOR, AUDIT FEE, DAN KUALITAS AUDIT (Studi Empiris pada Perusahaan Nonkeuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Siregar, Addinulsyah; Rohman, Abdul (Diponegoro Journal of Accounting, 2024)
This research aims to determine the effect of audit committee chair characteristics, consisting of gender, expertise, multiple positions and tenure, on decisions regarding auditor choice, audit fees and audit quality. The sample used in this research is non-financial companies listed on the Indonesia Stock Exchange in the 2019-2022 period. The total final sample used in this research was 781 firm-year observations. Sample selection was carried out using a purposive sampling method with predetermined conditions and criteria. In addition, the control variables used include audit committee size, gender of audit committee members, firm size, leverage, profitability, and company losses. The analytical methods used in this research are logistic regression analysis and multiple regression analysis.The results of this research found that the financial expertise of the audit committee chairman has a negative effect on audit quality. Furthermore, the results of this research also show that the expertise of the audit committee chair influences the selection of auditors for the company and the determination of audit fees. In addition, audit committee size, company size, and leverage have a positive effect on auditor selection and audit fee determination. Profitability only influences auditor selection.